2012
DOI: 10.3354/meps09972
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of three sympatric seabirds to spatio-temporal variability in shared resources

Abstract: Environmental change linked to climate and human activities may affect top predators via the food chain in marine systems. Understanding the functional link between resources and predator responses (e.g. foraging effort, reproductive success, population growth) is of crucial importance in the context of an ecosystem-based approach to fisheries. In the Benguela upwelling ecosystem located off the South African coast, both climate and overfishing may have modified the spatio-temporal availability of sardines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…By contrast, a lesser mobility and less adaptable diet of African Penguins and Cape Cormorants rendered them susceptible to a reduced local availability of prey (e.g. Durant et al 2010;Sabarros et al 2012;Sherley et al 2013). Both African Penguins and Cape Cormorants suffered high adult mortality in the last decade (Waller and Underhill 2007;Crawford et al 2011;Sherley et al 2014 Crawford et al 2009bCrawford et al , 2012Crawford et al , 2013Crawford 2013).…”
Section: Discussionmentioning
confidence: 91%
“…By contrast, a lesser mobility and less adaptable diet of African Penguins and Cape Cormorants rendered them susceptible to a reduced local availability of prey (e.g. Durant et al 2010;Sabarros et al 2012;Sherley et al 2013). Both African Penguins and Cape Cormorants suffered high adult mortality in the last decade (Waller and Underhill 2007;Crawford et al 2011;Sherley et al 2014 Crawford et al 2009bCrawford et al , 2012Crawford et al , 2013Crawford 2013).…”
Section: Discussionmentioning
confidence: 91%
“…At this time, food availability is high due to the presence of dense shoals of sardines and anchovies spawning near the coast (Sabarros et al 2012 ). In contrast, at the end of breeding, high mortality is observed in juvenile gannets that migrate from the coast of southwestern Africa, up the western and eastern coasts of Africa, to tropical waters following shoals of sardines (Broekhuysen et al 1961 ).…”
Section: Comparison With Seasonal Breeding In Other Eastern Boundary mentioning
confidence: 99%
“…For instance, Kitaysky and Golubova (2000) showed that climate change differentially influenced reproductive performance of sympatric alcid species depending on their foraging strategy (e.g., planktivorous vs. piscivorous). Other studies have also addressed the influence of environmental variation in some seabird communities and the specific effects on each species relative to their particular ecology (Sydeman et al, 2001;Sabarros et al, 2012). Even for the same species in different studies, results are not always similar (see Table 1), suggesting differences among populations (Tavecchia et al, 2008) or raising doubts about the suitability of selected climate indexes, the temporal window analyzed or the power of each data set to detect associations between climate and the seabird parameter of interest, especially when these associations are not statistically significant (Jenouvrier, 2013).…”
Section: Pitfalls and Gaps Of The Climate-seabird Researchmentioning
confidence: 99%